Pengaruh Pendidikan Kewirausahaan dan Lingkungan Keluarga terhadap Minat Berwirausaha Mahasiswa Kota Samarinda - Ghanaya Catur Famila; Reza Reza; Ratna Fitri Astuti (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2021)
The purpose of this study was to determine how the influence of entrepreneurship education and family environment on student entrepreneurship interest. The analytical method used in this research is using multiple regression analysis, then data collection was done by distributing questionnaires to 110 students in the city of Samarinda to find out the responses given regarding the interest in entrepreneurship, entrepreneurship education and the student's family environment. Based on the results of the t test, the sig value is 0.000 < 0.05 and the tcount = 7.182 > ttable = 1.982, so there is a partial and significant effect between entrepreneurship education on student entrepreneurship interest, then the sig value is 0.093 > 0.05 and the tcount = 1.695 < t table = 1.982 then there is no partial and significant influence between the family environment on the interest in entrepreneurship. Based on the results of the f test, the sig value is 0.000 < 0.05 and the Fcount = 65.693 > Ftable = 3.08, so it can be concluded that entrepreneurship education and family environment have a simultaneous and significant effect on student entrepreneurship interest in Samarinda City